Selection of Material Handling Equipment using the AHP and MOORA - Sule I Satoglu; İbrahim Türkekul (Jurnal Teknik Industri, 2021)
Choosing the best Material Handling Equipment (MHE) is an aspect that needs to be considered in the industrial sector because the amount of capital involved in the procurement process is very large. Many substantial factors influence the MHE selection process. One popular approach was chosen to resolve the MHE selection issue. The concept of Multi-Criteria Decision Making (MCDM) is popularly used because it can solve and handle conflicting components in the MHE selection process. This study proposes the Analytical Hierarchy Process (AHP) and Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) procedures in MHE selection. AHP is proposed to weigh the MHE selection criteria. MOORA is proposed to compute the rankings of the MHE alternatives. Case studies are applied to this problem. The results show that the cost criterion gives the greatest weight in selecting MHE. Other than that, Of the five selected MHE alternatives, Hand Pallet Truck is the MHE that has the best rating.